Association of sex hormones with incident 10-year cardiovascular disease and mortality in women. Issue 4 (December 2015) - Schaffrath, Gotja; Kische, Hanna; Gross, Stefan; Wallaschofski, Henri; Völzke, Henry; Dörr, Marcus; Nauck, Matthias; Keevil, Brian G.; Brabant, Georg; Haring, Robin
Highlights: Associations between sex hormones and incident 10-year cardiovascular disease and mortality were studied in a population-based sample of 2219 women with a mean age of 49 years at baseline. Levels of sex hormones were measured using liquid chromatography-tandem mass spectrometry, which is more accurate than the immunoassay methods used in previous studies. An inverse association between sex hormone binding globulin and cardiovascular disease was found at baseline, but no consistent associations were found between sex hormones and incident cardiovascular disease or mortality risk. Abstract: Objectives: The aims of this study were to ascertain whether women with high levels of serum total testosterone (TT) or low levels of sex hormone-binding globulin (SHBG) are more likely to develop cardiovascular disease (CVD), and to investigate potential associations between sex hormones and mortality (all-cause, as well as cause-specific) in the general population. Study design and main outcome measures: Data on 2129 women with a mean age of 49.0 years were obtained from the population-based Study of Health in Pomerania over a median follow-up of 10.9 years. Associations of baseline levels of TT, SHBG, and rostenedione (ASD), and free testosterone (fT), and of the free androgen index (FAI), with follow-up CVD morbidity, as well as all-cause and CVD mortality, were analyzed using multivariable regression modeling. Results: At baseline the prevalence rate of CVD was 17.8% (378 women) and the incidence of CVD over the follow-up was 50.9 per 1000 person-years. We detected an inverse association between SHBG and baseline CVD in age-adjusted models (relative risk per standard deviation increase: 0.83; 95% confidence interval: 0.74–0.93). We did not detect any significant associations between sex hormone concentrations and incident CVD in age- and multivariable-adjusted Poisson regression models. Furthermore, none of the sex hormones (TT, SHBG, ASD, fT, FAI) were associated with all-cause mortality. Conclusions: This population-based cohort study did not yield any consistent associations between sex hormones in women and incident CVD or mortality risk.